Kontribusi Gaya Belajar Terhadap Minat Belajar Siswa Selama Masa Pandemi Covid-19 Di Madrasah Ibtidaiyah Anwarul Hidayah - Hana Lestari; Siska Putriani; Ima Rahmawati (JURNAL KAJIAN ISLAM MODERN, 2022)
This study aims to determine the contribution of learning styles to interest in learning at Madrasah Ibtidaiyah Anwarul Hidayah. The method used in this study is the correlational method to know the contribution of learning styles to the learning interest of SD/MI students, as well as predict the contribution of learning styles to interest in learning. The instrument used in this research is a questionnaire, the questionnaire used is a closed questionnaire with a Likert scale, distributed a questionnaire to 127 students consisting of grades IV, V, and VI, at MI. The data obtained were analyzed using the Simple Linear Regression test using SPSS 25 at (0.05). The results show that online learning styles and offline learning styles have a major contribution if the learning style increases, the interest in learning will increase, and vice versa if the learning style decreases, the interest in learning decreases, this is evidenced by the probability value (sig) of 0.000 with an F value. amounted to 41222,917. the probability obtained is smaller than a significance of 0.05, which means that there is a significant contribution between online learning styles and online learning interest and a probability value (sig) of 0.000 with an F value of 70302.058. the probability obtained is smaller than a significant of 0.05, which means that there is a contribution between offline learning styles and offline learning interests. From these results, it can be concluded that online learning styles and offline learning styles have a major contribution if the learning style increases, the interest in learning will increase and vice versa if the learning style decreases, the interest in learning decreases.